7y+2(y-5)=5(y+2)-5

Simple and best practice solution for 7y+2(y-5)=5(y+2)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+2(y-5)=5(y+2)-5 equation:


7y+2(y-5)=5(y+2)-5

We simplify the equation to the form, which is simple to understand
7y+2(y-5)=5(y+2)-5

Reorder the terms in parentheses
7y+(+2y-10)=5*(y+2)-5

Remove unnecessary parentheses
+7y+2y-10=+5+*(+y+2+)-5

Reorder the terms in parentheses
7y+2y-10=+(+5y+10)-5

Remove unnecessary parentheses
+7y+2y-10=+5y+10-5

We move all terms containing y to the left and all other terms to the right.
+7y+2y-5y=+10-5+10

We simplify left and right side of the equation.
+4y=+15

We divide both sides of the equation by 4 to get y.
y=3.75

See similar equations:

| 3w^2-23w-13=0 | | 5(2q)+(q-4)+q=5 | | 9x+5y+0.1z=100 | | 2(6)(h)+2(h)(17)+2(6)(17)=342 | | 6x=x+6 | | 2(6)(h)+2(h)(17)+2(6)(17)=h | | 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= | | 0.29=logx | | x=log(3)(48) | | 3/4t-6=1/3t-1 | | 3/2t-6=1/3t-1 | | nx+b=6(x-n)forx |

Equations solver categories